Future of Freshwater Ecosystems in a 1.5°C Warmer World - Capon, Samantha J.; Stewart-Koster, Ben; Bunn, Stuart E. (Frontiers in Environmental Science, 2021)
Freshwater ecosystems are highly vulnerable to global warming because 1.) their chief drivers, water quality and flow regimes, are highly sensitive to atmospheric warming, and 2.) they are already extremely threatened by a wide range of interacting anthropogenic pressures. Even relatively modest global warming of 1.5C poses a considerable threat to freshwater ecosystems and the many critical services these provide to people. Shifts in the composition and function of freshwater ecosystems are widely anticipated with adverse consequences for ecosystem services, including those underpinning water and food security. While the extent and severity of effects is likely to be significantly reduced if global warming is limited to 1.5C, concerted efforts to implement widely recognised priorities for policy and management are required to mitigate unavoidable impacts and reduce the likelihood of perverse outcomes of climate mitigation and adaptation efforts in other sectors – all of which rely on fresh water supply. Freshwater ecosystems and their services, including provision of fresh water, must therefore be considered first and foremost when developing and implementing any climate action.